Risk factors, survival analysis, and nomograms for high-grade endometrial stromal sarcoma patients with distant metastasis: a population-based study (2010–2019) - Wang, Cheng; Liang, Dongni; Kuang, Wei; Sun, Huanxin; Kou, Yuling; Wang, Wei; Zeng, Jing (Frontiers in Oncology, 2025)
BackgroundHigh-grade endometrial stromal sarcoma (HGESS) is a rare, aggressive malignant tumor that often metastasizes early and is associated with a poor prognosis. This study aimed to develop a nomogram to predict the risk factors for distant metastases and the prognostic factors at the time of initial diagnosis.MethodsData on patients diagnosed with HGESS from 2010 to 2019 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Patients were randomly divided into the training and validation sets. Univariate and multivariate regression analyses were conducted to identify significant independent risk factors for distant metastases in HGESS patients, and univariate and multivariate Cox regression analyses were used to identify prognostic factors of HGESS patients with distant metastases. The Akaike information criterion (AIC) was used to further refine variables and construct a nomogram for predicting overall survival (OS) of HGESS patients with distant metastases. Two nomograms were developed and evaluated using receiver operating characteristic (ROC) curves, calibration plots, decision curves analysis, and concordance-index (C-index). In addition, Kaplan-Meier (KM) analysis was performed to evaluate OS in both the entire cohort and the metastasis cohort.ResultsA total of 360 HGESS patients were included, of whom 89 patients (24.7%) had distant metastases at initial diagnosis. Risk factors for distant metastases in HGESS patients included race, tumor size, T stage, and N stage. Prognostic factors for distant metastasis in HGESS patients included N stage and systemic therapy. Three variables - age, N stage and systemic therapy - were incorporated to construct the nomogram for predicting prognosis. The C-indexes for the training and validation sets were 0.776 and 0.710, respectively. In the entire cohort, significant differences in median OS were observed for tumor size, Federation International of Gynecology and Obstetrics (FIGO) stage, number of nodes examined, surgery, and radiotherapy. In metastasis cohort, significant differences in median OS were observed for N stage, surgery, chemotherapy, and systemic therapy.ConclusionsThe two nomograms developed in this study accurately predict the occurrence and prognosis of HGESS patients with distant metastases, which may aid clinical decision-making.